From bioprocess to market: Optimizing medium-chain carboxylate extraction for application readiness - Yiran Zhang; Aijie Wang; Yilu Sun; Xuening Zhang; Jianfeng Liu; Wen Wang; Cong Huang; Shaoping Fu; Honggang Deng; Yongping Shan; Jiadong Yu; Xufeng Yuan; et al. (Bioresource Technology, 2026)

Scale drop disease virus (SDDV) triggers ferroptosis both in mandarin fish (Siniperca chuatsi) and MFF-1 cells to facilitate virus infection via linking to transferrin receptor 1 (TfR1) - Jiaming Chen; Yuting Fu; Shuyi Chen; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

Structural characterization and prebiotic activity evaluation of novel fucosylated disaccharides prepared from bacterial exopolysaccharides - Shihao Nan; Xinmiao Ren; Mengshi Xiao; Lin Zhu; Haijin Mou; Ningyang Li; Rong Li; Shaoping Nie; Xiaodan Fu (Food Bioscience, 2024)

Construction of a cold island network for the urban heat island effect mitigation - Fan Liu; Jing Liu; Yanqin Zhang; Shaoping Hong; Weicong Fu; Minhua Wang; Jianwen Dong (Science of The Total Environment, 2024)

Development and characterization of a spleen cell line from yellowfin seabream Acanthopagrus latus and its susceptibility to Mandarinfish ranavirus - Zhipeng Zhan; Jiajie Fu; Huiquan Chen; Hongbo Pan; Shaoping Weng; Jianguo He; Changjun Guo (Journal of Fish Diseases, 2023)
Yellowfin seabream ( Acanthopagrus latus ) is one of the most commercially important marine fish in China. In this study, a new continuous cell line, named ALS cells, was developed from the spleen tissue of A. latus . The cell line was maintained in Dulbecco's modified Eagle medium/Nutrient Mixture F‐12 Ham (DMEM/F‐12) supplemented with 10% fetal bovine serum (FBS) and successfully cultured up to 50 passages. The cell line was authenticated by amplifying and sequencing mitochondrial cytochrome C oxidase subunit‐I ( coi‐I ) gene. The ALS cell line had the maximum growth rate in DMEM/F‐12 medium containing 20% FBS at 27°C. Chromosome number analysis showed that the ALS cells have a modal diploid chromosome number of 34. The ALS cell line was transfected with the pEGFP‐N1 plasmid, and green fluorescence was observed. The ALS cell line was used for testing Mandarinfish ranavirus (MRV) susceptibility, and the cytopathic effects in the cell line were observed at 4 days post‐infection (dpi). Furthermore, the susceptibility of the ALS cell line to MRV and the levels of MRV mRNA and viral loads were found to be significantly increased at 1–7 dpi. This study revealed that the ALS cell line could be useful for molecular, virological, and biotechnological studies on yellowfin seabream.

A mandarinfish Siniperca chuatsi infection and vaccination model for SDDV and efficacy evaluation of the formalin-killed cell vaccine in yellowfin seabream Acanthopagrus latus - Yuting Fu; Yong Li; Jiaming Chen; Fangzhao Yu; Xiangrong Liu; Weixuan Fu; Hongrun Pan; Wangdong Li; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

Effectively protecting Asian seabass Lates calcarifer from ISKNV-I, ISKNV-II, RSIV-II and SDDV by an inactivated ISKNV-I and SDDV bivalent vaccine - Yuting Fu; Yong Li; Wenfeng Zhang; Weixuan Fu; Wangdong Li; Zhiming Zhu; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

Production and characterization of monoclonal antibodies against mandarinfish ranavirus and first identification of pyloric caecum as the major target tissue - Wenfeng Zhang; Hengwei Deng; Yuting Fu; Weixuan Fu; Shaoping Weng; Jianguo He; Chuanfu Dong (Journal of Fish Diseases, 2023)
Mandarinfish ranavirus (MRV), also known as a variant of largemouth bass virus (LMBV), is an emerging pathogen in mandarinfish aquaculture. In this study, monoclonal antibodies (mAbs) against MRV were produced and characterized, and 7 mAbs were obtained through Western blotting screening and all 7 mAbs specifically recognized MRV/LMBV but not several piscine iridoviruses as ISKNV, GIV and TFV. By LC MS/MS analysis, the recognized viral proteins by seven mAbs were identified as MRV‐pORF47L, MRV‐pORF55R, MRV‐pORF57L, MRV‐pORF77L and MRV‐pORF78L, respectively, and all five viral proteins are late expression structural proteins by Western blotting. Based on mAb 1C4, immuno‐histochemistry and immuno‐histo‐fluorescence were performed to re‐assess the tissue tropism of MRV. The result showed that abundant reactive signals were observed in infected spleen, kidney as well as intestine and pyloric caecum. Real‐time quantitative PCR also demonstrated that spleen as well as pyloric caecum and intestines are the major target tissue upon MRV infection. In infected intestines and pyloric caecum, numerous enlarged, multinucleated cells with intracytoplasmic inclusions were identified as the target cells of MRV, suggesting that MRV serves as a digestive tract pathogen to mandarinfish, which may explain why acute infection of MRV can cause the typical clinicopathology featured by severe ascites.

The Sesuvium portulacastrum Plasma Membrane Na+/H+ Antiporter SpSOS1 Complemented the Salt Sensitivity of Transgenic Arabidopsis sos1 Mutant Plants - Yang Zhou; Xiaochang Yin; Shumin Wan; Yanping Hu; Qing Xie; Ruimei Li; Baibi Zhu; Shaoping Fu; Jianchun Guo; Xingyu Jiang (Plant Molecular Biology Reporter, 2018)

The novel Na+/H+ antiporter gene SpNHX1 from Sesuvium portulacastrum confers enhanced salt tolerance to transgenic yeast - Yang Zhou; Chenglong Yang; Yanping Hu; Xiaochang Yin; Ruimei Li; Shaoping Fu; Baibi Zhu; Jianchun Guo; Xingyu Jiang (Acta Physiologiae Plantarum, 2018)

Recombinant expressions of sweet plant protein mabinlin II in Escherichia coli and food-grade Lactococcus lactis - Wenliang Gu; Qiyu Xia; Jing Yao; Shaoping Fu; Jianchun Guo; Xinwen Hu (World Journal of Microbiology and Biotechnology, 2015)

Isolation and characterization of a C-repeat binding factor (CBF)-like gene in cassava (Manihot esculenta Crantz) - Ruimei Li; Yimeng Ji; Jie Fan; Chenglong Yang; Yuan Yao; Yang Zhou; Ruijun Duan; Jiao Liu; Shaoping Fu; Xinwen Hu; Jianchun Guo (Acta Physiologiae Plantarum, 2014)

Factors influencing direct shoot regeneration from mature leaves of Jatropha curcas, an important biofuel plant - Chao Zhang; Shaoping Fu; Gaijuan Tang; Xinwen Hu; Jianchun Guo (In Vitro Cellular & Developmental Biology - Plant, 2013)